Penguatan Karakter Islami dan Kepedulian Lingkungan melalui Perpustakaan dan TOGA di Sekolah Desa Karang Anyar - Wulida Emeris; Juli Maini Sitepu (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The formation of Islamic character and environmental awareness is an integral part of the national education goals which are oriented towards developing the personality of students as a whole. In rural schools, such as the free school in Karang Anyar Village, limited learning facilities often become a challenge in implementing character education based on Islamic and environmental values. This study aims to analyze efforts to strengthen Islamic character and environmental awareness through the use of school libraries and family medicinal plant (TOGA) planting activities as contextual learning tools. The research used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation during the real work lecture (KKN) program. Data analysis is carried out through a process of reduction, presentation, and drawing conclusions in order to obtain an in-depth picture of the effectiveness of the activity. The results of the study show that literacy activities in the library are able to increase reading interest, Islamic insight, and the habituation of religious attitudes among students. Meanwhile, TOGA activities contribute to the formation of attitudes of responsibility, mutual cooperation, and concern for the school environment. The synergy between these two activities has proven effective in strengthening Islamic character values ​​and environmental awareness, as well as creating a school culture that is religious, productive, and ecologically aware.